Internship in a business school: expectation versus experience. Issue 1 (4th December 2018) - Neelam, Netra; Bhattacharya, Sonali; Kejriwal, Vishakha; Bhardwaj, Varsha; Goyal, Anshul; Saxena, Arushi; Dhawan, Deeksha; Vaddi, Aditya; Choudaha, Garima
Abstract : Purpose: The purpose of this paper is to evaluate the value of internship as a function of the disparity between the initial expectation from the internship and its actual experience. The perceived internship experience has been evaluated through the expectation confirmation theory (ECT). Design/methodology/approach: A sample of 106 students pursuing Master of Business Administration in a business school in India were administered a questionnaire to assess their expectations and experience before and after the internship. The self-designed questionnaire based on review of extant literature on internship included items related to supervisor–intern exchanges, significance of prior classroom academic preparation, prior work experience and perceived learning value. Students' assessment scores on the internship project were taken as the outcome variable. Findings: Pre- and post-analysis of perceived internship value indicated a positive expectation disconfirmation. The result indicates that "Positive Expectation Disconfirmation" has a significant direct relationship with overall satisfaction with internship. Structural equation modeling further revealed that perceived quality of the supervisor–intern exchange has a significant relationship with perceived internship value. Perceived significance of classroom academic preparation has a weak negative relationship with both perceived internship value and internship performance. Perceived internship value has a weak positive relationship with internship performance. Originality/value: It is first time an attempt has been made to look into the issue of internship from the ECT.